Meta-analysis of the association between sclerostin level and adverse clinical outcomes in patients undergoing maintenance haemodialysis - Sha-Sha Li; Zhi-Qin Zhang; Da-Wei He; Ao-Lin He; Qi-Feng Liu (SAGE Publishing, 2021)
Background: Studies regarding the relationship of sclerostin (Scl) with clinical outcomes in patients undergoing maintenance haemodialysis have yielded controversial findings. This meta-analysis was performed to investigate the predictive role of Scl in this patient population. Methods: Several electronic medical databases (e.g. PubMed, Embase, Web of Science and Cochrane Library) were searched for eligible studies through December 20, 2019. Summary hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated based on Scr level (high or low) using a random or fixed effects model. Results: From among 641 initially screened publications, 16 eligible studies were included in this meta-analysis. A high Scl level was not associated with cardiovascular events [HR = 0.8 (95% CI, 0.42-1.35)] or all-cause mortality [HR = 0.93 (95% CI, 0.56-1.54)]. There was high heterogeneity, but no evidence of publication bias. Interestingly, a high Scl level was associated with reduced cardiovascular events [HR = 0.44 (95% CI, 0.29-0.69)] in the subgroup by shorter follow-up period or all-cause mortality [pooled HR = 0.58 (95% CI, 0.36-0.91)] by shorter dialysis vintage. Conclusion: This meta-analysis indicated that a high Scl level did not predict total clinical outcomes in patients undergoing maintenance haemodialysis despite survival benefits in the subgroups. The predictive role of Scl in these patients should be further evaluated in large prospective studies.